2007
DOI: 10.1200/jco.2007.12.0949
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Cetuximab, Bevacizumab, and Irinotecan Compared With Cetuximab and Bevacizumab Alone in Irinotecan-Refractory Colorectal Cancer: The BOND-2 Study

Abstract: Cetuximab and bevacizumab can be administered concurrently, with a toxicity pattern that seems to be similar to that which would be expected from the two agents alone. This combination plus irinotecan also seems to be feasible. The activity seen with the addition of bevacizumab to cetuximab, or to cetuximab plus irinotecan, seems to be favorable when compared with historical controls of cetuximab or cetuximab/irinotecan in patients who are naïve to bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
196
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(206 citation statements)
references
References 8 publications
2
196
2
6
Order By: Relevance
“…After irinotecan failure, this combination increased the response rate and prolonged the time to progression (response rate was 37% vs 23% and median time to progression 7.9 months vs 5.6 months). 12 The combination therapy with cetuximab after the failure of the conventional therapy increases resectability rates without increasing operative mortality or liver injury. Adam and colleagues showed that 7% of patients treated with cetuximab after the failure of the conventional therapy experienced a treatment response that allowed curative hepatectomy.…”
Section: Metastatic Colorectal Cancer (Crc)mentioning
confidence: 99%
“…After irinotecan failure, this combination increased the response rate and prolonged the time to progression (response rate was 37% vs 23% and median time to progression 7.9 months vs 5.6 months). 12 The combination therapy with cetuximab after the failure of the conventional therapy increases resectability rates without increasing operative mortality or liver injury. Adam and colleagues showed that 7% of patients treated with cetuximab after the failure of the conventional therapy experienced a treatment response that allowed curative hepatectomy.…”
Section: Metastatic Colorectal Cancer (Crc)mentioning
confidence: 99%
“…13 Early preclinical and clinical studies have suggested that blocking both angiogenesis and EGFR may enhance therapeutic efficacy. [14][15][16][17][18][19] Moreover, cetuximab in combination with chemotherapy improves survival of patients with colorectal cancer. 20,21 Therefore, the combination of chemotherapy with anti-EGFR antibodies has been studied in Phase III clinical trials.…”
mentioning
confidence: 99%
“…90 Several clinical studies are ongoing to evaluate the combination of cetuximab with bevacizumab (anti-VEGF Mab) after the encouraging preliminary results of Saltz et al 91 Another approach involves the association of cetuximab with small molecule tyrosine kinase inhibitors (TKIs) such as erlotinib, 92 gefitinib 93 and lapatinib. 94 …”
Section: Resultsmentioning
confidence: 99%